(untitled) (Patan Pragya, 2025)
This research has investigated the occurrences, frequency, and institutional reactions to misogyny and sexual harassment in Nepal’s Higher Education Institutions (HEIs). Utilizing a mixed-methods strategy targeting students and staff from both public and private colleges with few comprehensive interviews with the stakeholders— the study has examined types of harassment, obstacles to reporting, policy efficiency, and effects on academic involvement and professional paths. The findings of the study imply ongoing gendered power disparities; under-reporting linked to stigma and fear of backlash, and varied institutional responses. The paper ends with policy suggestions for universities, regulatory agencies, and civil society. Nepalese colleges must adopt and promote a zero-tolerance stance against harassment, highlighting that such actions lead to severe repercussions. This can be accomplished by employing display boards, posters, and awareness campaigns that effectively convey the institution’s position on harassment. Moreover, implementing periodic feedback surveys can offer important information regarding the experiences of female students, enabling colleges to grasp the difficulties they encounter. Creating an environment where women feel safe to voice their concerns without the fear of stigma is vital, promoting a culture of openness and support. By tackling these problems methodically, colleges can aid in fostering a safer and more welcoming learning environment.